Selection in guinea pigs: I. Estimation of phenotypic and genetic parameters for litter size and body weight get access arrow - Quijandria, B.; Chauca Francia, Lilia Janine; Robison, O. W. (American Society of Animal Science, 2023)
Data on 202 sires, 718 dams and 3,192 progeny from a selection experiment were used to estimate phenotypic and genetic parameters for litter size and body weight in guinea pigs. Effects of sex and parity were estimated. Heritability estimates were obtained from offspring-parent regression and from intraclass correlation of paternal and maternal half-sibs. Genetic and phenotypic correlations also were estimated. Parity effects were significant only for weight traits. Sex effects were significant for weights at several ages. Significant negative linear effects of number born alive were found for birth, weaning and 13-wk weights. Heritability estimates from daughter-dam regression were .10 ± .05, .06 ± .02 and .08 ± .02 for number born, number born alive and number weaned and .12 ± .03, -.13 ± .03 and .12 ± .02 for birth, weaning and 13-wk weights, respectively. Paternal half-sib heritability estimates were .02 ± .04, .10 ± .04 and .17 ± .05 for birth, weaning and 13-wk weights. Heritability values from components for maternal half-sibs were .30 ±.30, .16 ±.31 and .15 ± .31 for number born, number born alive and number weaned, respectively. Genetic correlations among weights at different ages were .24 to 1.2 and among litter size traits were .51 to .77. Genetic correlations between litter size traits and birth and weaning weights ranged from -.61 to -.97; whereas correlations of litter size traits with 13-wk weight were .31 to .39. Genetic parameters estimated from similarity among relatives agreed very well with realized heritabilities and genetic correlations obtained from selection.